The value of 3D pseudo-continuousarterial spin labeling perfusion imaging in moyamoya disease—Comparison with dynamic susceptibility contrast perfusion imaging - Zhang, Hongtao; Lu, Mingming; Liu, Shitong; Liu, Dongqing; Shen, Xuxuan; Sheng, Fugeng; Han, Cong; Cai, Jianming (Frontiers in Neuroscience, 2022)
Background and purpose 3D pseudo-continuous arterial spin labeling (3D pCASL) is commonly used to measure arterial cerebral blood flow (CBF). The aim of this study was to assess the clinical feasibility and accuracy of 3D pCASL in comparison with dynamic susceptibility contrast (DSC) perfusion imaging in moyamoya disease (MMD). Materials and methods A total of 174 MMD patients underwent 3D pCASL and DSC-MRI for evaluating cerebral blood perfusion. 3D-pCASL with two single post-labeling delay (PLD) times (1,500 and 2,500 ms) was used to measure CBF. The values of DSC-CBF and ASL-CBF were calculated for major arterial territories including the anterior, middle, and posterior cerebral arteries as well as the areas based on the Alberta Stroke Program Early CT Score (ASPECTS) template. The correlation between DSC-CBF and ASL-CBF was analyzed. The consistency and accuracy between the two methods in assessing the cerebral ischemic state before and after surgery were analyzed. Results The correlation between ASL (2,500 ms) and DSC-MRI was slightly better than the correlation between ASL (1,500 ms) and DSC-MRI in major vascular territories before revascularization. Significant correlations were observed between ASL (2,500 ms) and DSC-MRI and between ASL (1,500 ms) and DSC-MRI in major vascular territories after revascularization. For 44 surgically treated patients, the scores of ASPECTS for CBF on the operated side were significantly different before and after revascularization (p < 0.05) and showed good consistency on all the examination methods. A comparison of the scores of ASPECTS of the three parameters before and after revascularization showed that there was no statistical difference between them (p > 0.05). Conclusion Compared to DSC-MRI, 3D pCASL can assess the cerebral blood perfusion in MMD before and after revascularization effectively. 3D pCASL showed the feasibility and clinical utility value in patients with MMD.